Bioactive Titanium Surfaces Enriched with Silver Nanoparticles Through an In Situ Reduction: Looking for a Balance Between Cytocompatibility and Antibacterial Activity. Issue 2 (1st October 2022) - Cazzola, Martina; Barberi, Jacopo; Ferraris, Sara; Cochis, Andrea; Cempura, Grzegorz; Czyrska-Filemonowicz, Aleksandra; Rimondini, Lia; Spriano, Silvia
Abstract : This research aims toward an antibacterial and osteoconductive Ti6 Al4 V surface by chemical etching–oxidation treatment and in situ reduction of silver nanoparticles. Starting from a previously developed process, already proved to enhance the osteoinductive ability of titanium, different parameters are changed to tailor the amount of silver and its distribution across the surface oxide layer thickness. The samples are characterized by scanning and transmission electron microscopy, energy‐dispersive X‐ray spectroscopy, release of silver, biofilm formation ( Staphylococcus aureus ), and cytocompatibility toward human osteoblasts progenitor cells. The total amount of silver in the surface oxide layer depends only on the concentration of the silver precursor. The time of the addition of the silver precursor, during the oxidation treatment, affects the oxide layer thickness, dimension, and distribution of the nanoparticles across the surface oxide: they are larger and accumulate on the outermost layer, if the addition occurs early. The maximum ion release occurs after 24 h and lasts up to 14 days; the later addition of silver precursors leads to sustaining the silver release for a longer time. The samples prepared with the higher concentration of the silver precursor are bactericide, but highly cytotoxic, whereas the other ones are bacteriostatic and moderately cytotoxic. Abstract : Osseointegration and peri‐implant infections are among major challenges for titanium‐based biomaterials. Surface treatments are applied to improve surface bioactivity and antibacterial properties. In situ reduction of silver nanoparticles is investigated during a chemical treatment on Ti6 Al4 V. Tuning the process parameters, nanoparticles of different dimensions along the cross section are obtained, obtaining good bacteriostatic capability and reduced cytotoxicity of the surface.